A REVIEW ON PALMYRA PALM (BORASSUS FLABELLIFER) - Gummadi, Veda Priya; Battu, Ganga Rao; M. S., Keerthana Diyya; Manda, Kiran (International Journal of Current Pharmaceutical Research, 2016)
The medicinal plants have very important role in the health of human beings as well as animals. India is the largest producer of medicinal plants. One such plant, Borassus flabellifer L, belongs to family Arecaceae, commonly known as Palmyra palm is a native of tropical Africa but cultivated throughout India. Traditionally the different parts of the plant such as root, leaves, fruit, and seeds are used for various human disorders. Leaves are used for thatching, mats, baskets, fans. Flowers of B. flabellifer were investigated for analgesic and antipyretic effects, anti-inflammatory activity, haematological, biochemical parameters, and immunosuppressant property. The different parts of the plant are being used for medicinal properties like antihelminthic and diuretic. The fruit pulp of B. flabellifer has been used in traditional dishes and the sap, has been used as a sweetener for diabetic patients. Phytochemical studies of the plant revealed the presence of spirostane-type steroid saponins; steroidal glycoside also contains a bitter compound called flabelliferrins. Although investigations have been carried out a lot more can still be explored, exploited and utilized. The present review highlights the phytochemical and pharmacological studies including folklore medicinal uses of this plant.